Adaptação transcultural da versão brasileira do Womens Use of the Internet in Pregnancy Questionnaire" - Ana Carolina Cleto Borges (2018)
Cross-cultural adaptation of the brazilian version of womens 'use of the internet in pregnancy questionnaire" There is a need for instruments, either created in Brazil or adapted to the Brazilian context, that assess the use of the Internet by pregnant women and its influence on the decision-making process related to health. The aim of the present study is to transculturally adapt the Womens Use of the Internet in Pregnancy Questionnaire (B-WUIPQ) and to evaluate the psychometric properties the Brazilian version of the "Preparedness for Decision Making" Scale (PDMS). WUIPQ was developed and validated in Northern Ireland and presents 71 items, 11 of which correspond to the PDMS, which evaluates the perception of the pregnant woman about the usefulness of the internet for health-related decision making and communication with the professional during prenatal consultations. The author of the questionnaire authorized the process of adaptation of WUIPQ to the Brazilian context. The target population of the study were 941 women, members of the virtual groups of pregnant women and mothers of Facebook@, who met the eligibility criteria: pregnant women and Brazilian mothers over 18 years of age who had children less than a year and residing in Brazil. The evaluation of the conceptual equivalence and questionnaire items was carried out by the panel of experts. The translation was performed independently two bilingual translators. After analysis of the two versions, the panel of experts created the synthesis version, which was back-translated into English by another bilingual translator and the back-translated version was submitted for the evaluation of the author of the original questionnaire. The adjustments carried out in the synthesis version resulted in the pre-test version. The pre-test version was applied to 151 female members of a virtual Facebook® group. For the study of the psychometric properties of the PDMS scale, the test-retest reliability was estimated by means of Intraclass Correlation Coefficient, applying the B-WUIPQ in a sample of 117 participants, members of four virtual groups. After the result, the questionnaire was applied to 673 pregnant women and mothers of 118 groups to evaluate the internal consistency and construct / structural validity, which were measured by Cronbach's alpha and Confirmatory Factor Analysis, respectively. The B-WUIPQ demonstrated evidence of the good comprehension of its content, as attested by the panel of experts and members of the target population. Most women in the pretest (88.14%) considered the items to be clear and pertinent to Brazilian culture and 84.09% evaluated the sequence of the questionnaire to be excellent/good. The Intraclass Correlation Coefficient of the Brazilian version of the PDMS scale was 0.85 (95% CI: 0.791-0.899) and Cronbachs alpha was 0.91. Confirmatory factorial identified explained 81% (IC 0,071- 0,092) of the variance and factor loads greater than 0.70 for most items. The results showed that the B-WUIPQ presented good semantic validation and the Brazilian version of the PDMS scale proved to be reliable and valid indicating the applicability of the scale in the Brazilian context. Keywords: Pregnant Women. Internet. Access to Information. Information Seeking Behavior. Questionnaire. Cross-Cultural Comparison